2007
DOI: 10.4081/ijas.2007.1s.728
|View full text |Cite
|
Sign up to set email alerts
|

Egg quality traits of laying hens reared in organic and conventional systems

Abstract: This study aims to compare the physico-chemical properties of eggs (weight, eggshell breaking strength, Haugh index, yolk colour, lipid, cholesterol, protein, ash and dry matter) laid either by hens reared according to the organic method or by caged hens kept in conventional system. More than 1,400 eggs have been analysed at the beginning, in the middle and at the end of the laying cycle in organic and conventional farms. The egg obtained from the organic system were lighter (64.4 vs 66.2 g) being yolk, albume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
32
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 3 publications
17
32
2
6
Order By: Relevance
“…The differences between FR and B values were highly significant, while the other comparisons (B vs. IC and IC vs. FR) showed (P <0.05) a significance threshold. Studies conducted by Minelli et al (2007) support our findings, stating that conventionally produced eggs are richer in cholesterol than organic ones, while Anderson (2011) and Shapira (2011) found that housing environment did not affect the inner cholesterol content of the eggs significantly, even if the free-range ones were slightly richer in this nutrient. Nevertheless, any excessive content of lipids and cholesterol in free-range eggs could be nutritionally counterbalanced by the lipid quality in such eggs, for example higher levels of n-3 PUFA in the yolks of free-range eggs, compared with deep litter ones (P <0.05) (Krawczyk & Gornowicz, 2010).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The differences between FR and B values were highly significant, while the other comparisons (B vs. IC and IC vs. FR) showed (P <0.05) a significance threshold. Studies conducted by Minelli et al (2007) support our findings, stating that conventionally produced eggs are richer in cholesterol than organic ones, while Anderson (2011) and Shapira (2011) found that housing environment did not affect the inner cholesterol content of the eggs significantly, even if the free-range ones were slightly richer in this nutrient. Nevertheless, any excessive content of lipids and cholesterol in free-range eggs could be nutritionally counterbalanced by the lipid quality in such eggs, for example higher levels of n-3 PUFA in the yolks of free-range eggs, compared with deep litter ones (P <0.05) (Krawczyk & Gornowicz, 2010).…”
Section: Resultssupporting
confidence: 77%
“…Minelli et al (2007) have reported different values for crude protein, in favour of organically produced eggs, (17.1% vs. 16.7%) compared with those from the conventional system. Lipid content varied significantly (P <0.05) from 10.78 ± 0.87% (FR eggs) to 11.4 ± 0.65% (B eggs), while IC eggs presented intermediate values (11.23 ± 0.9 % crude fat).…”
Section: Resultsmentioning
confidence: 99%
“…Yolks of hard boiled eggs from different production systems statistically significantly differ in colour shade, which is shown by values a* and b* ( Yolk colour in conventional eggs was significantly more red and significantly less yellow in comparison to yolks from organic eggs. Similar results for intensiveness of red and yellow yolk colour from conventional and organic eggs were also reported by Minelli et al (2007).…”
Section: Tab 2 Differences In Physical Characteristics Between Convsupporting
confidence: 76%
“…The same result was reported by Perić et al (2015a;2015b) who stated that eggs from organic production had higher fat content in yolks compared to eggs from conventional cages. On the contrary, Minelli et al (2007) did not find any difference in the fat content in yolk between free range and conventional eggs. It is important to emphasize that most of the research on nutritional composition of organic eggs has been directed at the fatty acid composition and the level of cholesterol rather than fat content (Samman et al, 2009).…”
Section: Discussionmentioning
confidence: 68%